Introduction - Buchenau, Jürgen (Anuario de Historia de América Latina, 2017)
One hundred years after its promulgation, it seems appropriate to take stock of the formulation and impact of the Constitution of 1917, a document soon thereafter eclipsed by the much more radical constitution of the Soviet Union and therefore the subject of relatively few scholarly analyses, especially with regard to transnational perspectives. Written by eminent historians from Canada, Germany, Great Britain, and Mexico, the six essays in this special section bring together different perspectives on the constitution and its international impact.